Corrosion behaviour of PEEK or β-TCP-impregnated Ti6Al4V SLM structures targeting biomedical applications - COSTA, M. M.; DANTAS, T. A.; BARTOLOMEU, F.; ALVES, N.; SILVA, F. S.; MIRANDA, G.; TOPTAN, F. [UNESP] (Elsevier, 2019)
Ti6Al4V cellular structures were produced by selective laser melting (SLM) and then filled either with beta-tricalcium phosphate (β-TCP) or PEEK (poly-ether-ether-ketone) through powder metallurgy techniques, to improve osteoconductivity and wear resistance. The corrosion behavior of these structures was explored considering its importance for the long-term performance of implants. Results revealed that the incorporation of open cellular pores induced higher electrochemical kinetics when being compared with dense structures. The impregnation of β-TCP and PEEK led to the creation of voids or gaps between the metallic matrix and the impregnated material which also influenced the corrosion behavior of the cellular structures.
Keywords: beta-tricalcium phosphate (β-TCP); corrosion; multimaterial design; poly-ether-ether-ketone (PEEK); Ti6Al4V cellular structures